Tipe dan Pola Reduplikasi Bahasa Rote - Boik, Susi Yanti; Hendrokumoro, Hendrokumoro (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to identify the types and patterns of reduplication in the Rote language. The methods used to collect data are the introspection method and the listening and note-taking method. The data sources of this study consist of oral data sources and written data sources. The collected data are analyzed using the distribution method and the direct element technique, then presented formally and informally, namely by using ordinary words and by using signs or symbols. The results of the study show that the types of reduplication of BR reduplication consist of the type of reduplication based on form, the type of reduplication based on foci, the type of reduplication based on directional elements, and the type of reduplication based on word classes. The type of reduplication of BR based on form is divided into two, namely full reduplication and partial reduplication. Full reduplication consists of full reduplication itself which occurs in all word classes, full reduplication with phoneme changes, namely vowel phonemes, and full reduplication with the addition of affixes. Meanwhile, partial reduplication is only found in verbs and adjectives. In addition, there are two types of reduplication based on foci: initial reduplication and final reduplication. Other types of BR reduplication include those based on direction, namely leftward reduplication and rightward reduplication, and those based on word class. This type of reduplication is seen in verbs, nouns, adjectives, adverbs, numerals, and interrogatives. There are also BR reduplication patterns: full reduplication, full reduplication with affixes, full reduplication with vowel or consonant changes, or both, prefix-syllable reduplication/leftward reduplication, suffix-syllable reduplication/rightward reduplication, CV-form reduplication, CV-form reduplication with affixes, CV-form reduplication, and KKKV-form reduplication.